2014
DOI: 10.1007/s13730-014-0151-0
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of severe crescentic lupus nephritis by multi-target therapy using tacrolimus and mycophenolate mofetil

Abstract: Treatment of severe lupus nephritis (LN) has been controversial, and according to recent guidelines and recommendations, cyclophosphamide still remains a firstline therapy. Herein, we present the case of a 37-year-old female patient who developed rapidly progressive glomerulonephritis, which was histologically diagnosed as class IV ? V LN, with a large number of cellular to fibrocellular crescents (62 % of glomeruli). Although the patient was considered to have the most severe form of LN, complete remission wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…In a randomised trial comparing intravenous cyclophosphamide and steroids with combined treatment of MMF, tacrolimus and glucocorticoids in LN, there was a greater number of patients achieving complete remission at 6 months in the combination group; however, patients with serum creatinine >265 µmol/L were excluded [ 53 ]. One patient with crescentic LN (61% crescents) was separately reported to have successfully entered remission using this multi-targeted approach [ 54 ].…”
Section: Lupus Nephritismentioning
confidence: 99%
“…In a randomised trial comparing intravenous cyclophosphamide and steroids with combined treatment of MMF, tacrolimus and glucocorticoids in LN, there was a greater number of patients achieving complete remission at 6 months in the combination group; however, patients with serum creatinine >265 µmol/L were excluded [ 53 ]. One patient with crescentic LN (61% crescents) was separately reported to have successfully entered remission using this multi-targeted approach [ 54 ].…”
Section: Lupus Nephritismentioning
confidence: 99%
“…Based on the therapeutic effects observed in the two groups in this study, the total effective rate of group A was much higher than that of group B. Lee et al ( 30 ) evaluated the comparative efficacy and safety of tacrolimus, mycophenolate mofetil, and cyclophosphamide in the inductive treatment of LN and found that the total effective rate of tacrolimus was much higher than that of mycophenolate mofetil and cyclophosphamide and that tacrolimus most likely reduced the risk of severe infection.…”
Section: Discussionmentioning
confidence: 78%
“…In this study, two combination treatments were compared, and the therapeutic effect of mycophenolate mofetil combined with tacrolimus was better than that of mycophenolate mofetil combined with cyclophosphamide in LN. Some studies showed that the multi-targeted therapy of tacrolimus combined with mycophenolate mofetil could be used to treat patients with severe crescent LN, whose symptoms were completely alleviated within 6 months ( 30 ). The time of effectiveness and time of effect validity of group A were much lower than those of group B.…”
Section: Discussionmentioning
confidence: 99%
“…RPGN can be a presentation of SLE, acute proliferative glomerulonephritis, Henoch-Schönlein purpura and IgA nephropathy. 1 Pulmonary signs of SLE may present with a various spectrum of diseases such as pleuritis, pneumonia, pulmonary embolism, pneumothorax and or pulmonary hemorrhage. [2][3][4] Immune complex deposition injury are the main player in pulmonary complications.…”
Section: Introductionmentioning
confidence: 99%